The Influence of the Ideas of Terrorism and Extremism in the Information Age on the Consciousness of Youth Through the Internet Media - Saidov Mionfarukh Rabiullaevich (Zien Journals, 2022)
The article describes spiritual, educational and educational measures aimed at preventing the introduction of the ideas of terrorism and extremism through the Internet and their negative impact on the minds of young people.
Keywords: Terrorism; extremism; international terrorism; Internet